2010
DOI: 10.1590/s0066-782x2010005000087
|View full text |Cite
|
Sign up to set email alerts
|

Obesidade e fatores de risco cardiovascular em adolescentes de escolas públicas

Abstract: Background: Overweight in adolescence is a risk factor for the development of cardiovascular diseases in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
(35 reference statements)
2
11
0
3
Order By: Relevance
“…This has raised the overweight rates among adolescents worldwide, since the consumption of foods with high energy content coupled with physical inactivity increase the body mass index. Given this, a study corroborated the data from this research and identified the positive influence between the values of body mass index and BP among adolescents, 18 demonstrating that increased BMI and WC are risk predictors for hypertension in adolescents. It is noteworthy that adolescents with overweight have the highest frequencies for cardiovascular risk factors, when compared to the eutrophic group.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This has raised the overweight rates among adolescents worldwide, since the consumption of foods with high energy content coupled with physical inactivity increase the body mass index. Given this, a study corroborated the data from this research and identified the positive influence between the values of body mass index and BP among adolescents, 18 demonstrating that increased BMI and WC are risk predictors for hypertension in adolescents. It is noteworthy that adolescents with overweight have the highest frequencies for cardiovascular risk factors, when compared to the eutrophic group.…”
Section: Discussionsupporting
confidence: 74%
“…However, this association was not identified by research that analyzed the same variables in subjects of the same age. 18 As for the increase in systolic and diastolic blood pressure in adolescents with overweight, a study did not identify significant difference between genders: systolic blood For these reasons, it is important to identify the risk factors associated with the ND overweight, since the time of exposure to several risk factors at this age to adulthood shows to be directly associated with morbidity from cardiovascular disease. Identifying that cardiovascular diseases may originate in childhood and adolescence leads to the need for extensive research of risk factors, in order to plan early and effective interventions to reduce morbidity and mortality from cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Of the overweight adolescents, 22.09% had more than three risk factors, as compared to 6.12% of the eutrophic group. 4 Overweight and obesity, as well as the related noncommunicable diseases, can be prevented. The World Health Organization (2015) recommends the choice of healthy foods and regular physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, physical fitness is one of the most important health status markers that predicts cardiovascular disease and mortality (Ortega, Ruiz, Castillo, & Sjostrom, 2008), mainly among overweight and obese individuals (Cobayashi, Oliveira., Escrivão, Silveira, & Taddei, 2010;Rodrigues, Perez, Carletti, Bissolli, & Abreu, 2007). In children and adolescents, physical fitness is associated with improved health-related biomarkers that may further influence young adulthood health (Foley, Quinn, Dwyer, Venn, & Jones, 2008;Simmons, Griffin, Steele, Wareham, & Ekelund, 2008).…”
Section: Introductionmentioning
confidence: 99%